Penerapan Pengendalian Internal dalam Audit Piutang Usaha untuk Meminimalisir Piutang Tak Tertagih pada Puskesmas - Ifanisari, Ameilia Budi; Widodo, Condro (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of internal control in the receivables audit process and evaluate its effectiveness in minimizing the risk of bad debts in a health center environment. Receivables, especially those originating from health services to JKN participants and general patients, can cause problematic receivables if not managed effectively. This study uses a descriptive qualitative approach with data collection through observation, interviews and documentation review during the audit by a public accounting firm. The results of the study indicate that there are still weaknesses in the internal control structure such as suboptimal separation of duties, an unintegrated receivables information system and a weak bad debt reserve policy. In addition, late payments by third parties and poor patient administration knowledge are also external factors that influence the high risk of bad debts. Therefore, improving the internal control system, implementing information technology and strengthening coordination with the guarantor are very important to reduce the risk of bad debts and increase accountability for financial management in the health center environment.